Psychometric testing of a Danish version of the empowerment of parents in the intensive care – Neonatology questionnaire has confirmed validity - Weis, J.; Beck, S.A.; Jensen, A.; Brødsgaard, A.; Latour, Jos; Greisen, G. (2023)
Aim: Investigating parent satisfaction with care is important to guide quality development. In this study, we translated and validated a Danish version of the empowerment of parents in the intensive care – neonatology (EMPATHIC-N) questionnaire to determine validity in Danish contexts. Method: A psychometric study design was applied. Translation was performed according to recommended international standards. Confirmatory factor analyses including standardised factor loadings, Cronbach's α reliability estimates, congruent validity and non-differential validity testing were applied. The study was performed from June 2017 to November 2019 at a 33-bed level IV neonatal intensive care unit. Results: Participants were 311 parents (response rate = 42,8%). Confirmative factor analyses disclosed a moderate model fit of the instrument with Comparative Fit Index (CFI) values of 0.83–0.92. Cronbach's α showed good reliability (0.82–0.93). Congruent validity showed good positive correlations (0.48–0.71) between the instrument domains and four overall satisfaction indicators. In search of improved model fit, a version including 27 items was tested. This version showed a better model fit with CFI values of 0.92–0.99 and satisfactory Cronbach's α values. Conclusions: Model fit for the Danish full EMPATIC-N was moderate. The shorter version showed better psychometric properties.